DESKRIPSI HISTOLOGIS DAN PERUBAHAN KOMPOSISI KIMIA DAUN DAN TANGKAI SEMANGGI (Marsilea crenata Presl., Marsileaceae) - Agoes Mardiono Jacoeb; Nurjanah .; Miftakhul Arifin; Widi Sulistiono; Stefanus Senoadi Kristiono (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2010)
Marsilea crenata is classified as hydrophytes plant growth in paddy's field, ponds, lakes, swamp or river and called semanggi as Javanese local name. The plant ethnobotanically used as food by steaming. The research was aimed to describe the histological and chemical composition of leaves and stems as well as the influence of steaming on chemical components. The result showed that the structures of stalks, stem and root were not equipped with collenchymas tissue. The cortexes consist of many aerenchym as well as the abaxial and adaxial laminas were equipped with a layer of epidermis and the stomata on the upper part of leaf. Leaves and stems contain water, ash, fat, protein, and crude fiber 89%, 2.70%, 4.35%, 2.28% (w/w), respectively. Steaming process reduced about 80% of ash content while the vitamins C, beta carotene and total carotenes content decreased about 17%, 37%, and 43%, respectively. The content of potassium as main mineral dropped 7% due to steaming process. The fresh leaves and stems of Marsilea crenata contain reducing sugar, steroid, carbohydrate, and flavonoids.Keywords: histology, leaf, Marsilea crenata, steaming, stem